Correction to: Special issue title: Optimization and mathematical modeling in energy systems (Energy Systems, (2021), 12, 4, (835-839), 10.1007/s12667-021-00443-x) - Saharidis, Georgios K.D.; Moza, Zoi; Golias, Mihalis (My University, 2021)
In the original publication of the article, four articles already published to other issues were incorrectly included. These articles are: 1. Nikolaidis, Pavlos & Chatzis, Sotirios & Poullikkas, Andreas. (2020). Optimal planning of electricity storage to minimize operating reserve requirements in an isolated island grid. Energy Systems. 11. https:// doi. org/ 10. 1007/ s12667- 019- 00355-x. 2. Touš, Michal & Máša, Vítězslav & Vondra, Marek. (2021). Energy and water savings in military base camps. Energy Systems. https:// doi. org/ 10. 1007/ s12667- 019- 00354-y. 3. Atsalakis, George & Frantzis, Dimitrios & Zopounidis, Constantin. (2015). Energy’s exports forecasting by a neuro-fuzzy controller. Energy Systems. 6. https:// doi. org/ 10. 1007/ s12667- 015- 0140-1. 4. Nazari, Amirali & Keypour, Reza. (2020). Participation of responsive electrical consumers in load smoothing and reserve providing to optimize the schedule of a typical microgrid. Energy Systems. 11. https:// doi. org/ 10. 1007/ s12667- 019- 00349-9. The special issue does not contain the above papers.